FACTORS AFFECTING THE PERFORMANCE OF SMES DURING COVID-19 AND THE ROLE OF SOCIAL MEDIA ADOPTION - Shirin Jamal Mohammad Rashid (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The purpose of this study was to investigate the factors affecting the adoption of social media by SMEs in the Kurdistan region. In addition, it also aimed to investigate the impact of social media adoption on the financial and non-financial performance of SMEs. The researcher used an integrated model for this research and analyzed the impact of trust, compatibility, and cost-effectiveness for social media adoption by SME owners using the diffusion of innovation theory. The findings of the study suggest that trust, compatibility, and cost-effectiveness have a positive and significant impact on the adoption of social media for firm performance in the Kurdistan region. Similarly, the results also show that social media adoption is crucial to the firm financial and non-financial performance in the Kurdistan region specifically due to the Covid-19 social distancing issue. The current study is limited to the Kurdistan region Erbil city only however, the future research can focus on a broader sample size. Future research can also focus on analyzing specific social media tools such as Facebook or Instagram to analyze the impact on the performance. Not many existing studies analyzed the impact of social media adoption during the pandemic while societies practice social distancing and are financially stagnated by the pandemic